Low-Cost Educational Materials. How to Make, How to Use, How to Adapt. Inventory. Volume II - United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and the Pacific; United Nations Educational, Scientific, and Cultural Organization, Bangkok (Thailand). Regional Office for Education in Asia and the Pacific ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1984)
This volume presents instructions for 61 low-cost and indigenous teaching materials that were developed from recommendations of the Fifth Regional Consultation Meeting on APEID (Asia and the Pacific Programme of Educational Innovation for Development) held in March 1978. Third in a series, this document describes materials that not only contribute to entertaining children, but to the achievement of several educational objectives, such as cognitive development, acquisition of manipulative skills, and individual and collective creativity. Each description lists the subject area, grade levels, objectives, materials needed, and the source. Instructions tell both how to make and how to use the item, and describe possible modifications when applicable. Educational games and toys are among the materials described, which include play activities or crafts for use in teaching basic science, physical education, storytelling and creative expression, basic arithmetic, mathematics, the language arts, music, physics, biology, and general science. Instructions are illustrated with line drawings. (DJR)
ERIC Note: Asia and the Pacific Programme of Educational Innovation for Development. For volumes I and II, see ED 205 166 and ED 237 059.
Microfiche.
Pomi
Keywords: Audiovisual Aids; Developing Nations; Educational Games; Foreign Countries; Handicrafts; Instructional Materials; Material Development; Production Techniques; Resource Materials; Teacher Developed Materials; Toys; Asia